Effects of the royal jelly consumption on post-stroke complications in patients with ischemic stroke: results of a randomized controlled trial - Karimi, Elham; Arab, Arman; Sepidarkish, Mahdi; Khorvash, Fariborz; Saadatnia, Mohammad; Amani, Reza (Frontiers in Nutrition, 2024)
Aims: There is a paucity of evidence regarding the benefit of royal jelly (RJ) on post-stroke complications in patients with ischemic stroke. To address this knowledge gap, this randomized, triple-blind, placebo-controlled clinical trial was carried out to determine the effects of RJ consumption on post-stroke clinical outcomes Methods: Of 64 eligible ischemic stroke patients (45-80 years), 32 were randomized to the RJ and 32 to the placebo groups and completed a 12-week intervention. The intervention group was advised to receive 1000 mg of RJ dragee daily after breakfast. Post-stroke complications including cognition, fatigue, mental health, and appetite, along with other criteria of serum levels of brain-derived neurotrophic factor (BDNF), and mid-upper arm circumference (MUAC) were assessed in groups pre-and post-intervention. Results: After 12 weeks of RJ consumption, cognitive function (adjusted mean difference, 4.71; 95% confidence interval [CI], 1.75 to 7.67), serum levels of BDNF (adjusted mean difference, 0.36; 95% CI, 0.05 to 0.67), stress (adjusted mean difference, -3.33; 95% CI, -6.50 to -0.17), and appetite (adjusted mean difference, 1.38; 95% CI, 0.19 to 2.56) were significantly improved. However, the findings for fatigue (adjusted mean difference, -4.32; 95% CI, -10.28 to 1.63), depression (adjusted mean difference, -1.71; 95% CI, -5.58 to 2.16), anxiety (adjusted mean difference, -2.50; 95% CI, -5.50 to 0.49), and MUAC (adjusted mean difference, 0.36; 95% CI, -0.11 to 0.84) were less favorable. Conclusions: Findings support the benefits of RJ consumption in improving post-stroke complications and clinical outcomes.